Critical Language Pedagogy in a Neoliberal Space (Hagwǒn) in Korea: Student Awareness and Engagement in Critical Dialogue - Cho, Wonguk (Critical Education, 2023)
Critical Pedagogy (CP) has been carried out in many contexts, and reports of its success in language teaching in various countries have increasingly appeared (Bennet 2018; West 2014). However, South Korea (henceforth Korea) is not well-known for critical inquiry in language education, especially in private language institutions, so-called hagwǒn. The Korean language education system still widely accepts the grammar-translation methodology and problem-solving techniques to prepare students for standardized tests, even though this system is considered a form of oppression by English learners (J. Park 2011). This might be thought as particularly the case in neoliberal spaces — not ideal for CP. Nevertheless, this study explores the possibility of adopting a CP framework in one such space, a Korean private language school. I investigate participants’ awareness of a Korean labor issue, their metaphorical language use for indicating power relations, and their recognition of the relationship between English and power. Through analyzing the participants’ critical dialogue using the framework of Critical Discourse Analysis, I conclude that students’ engagement with critical dialogue, an essential component of CP, is feasible. Thus, CP is applicable even in a neoliberal space such as a hagwǒn.